2004
DOI: 10.1093/nar/gkh348
|View full text |Cite
|
Sign up to set email alerts
|

Translational regulation of BACE-1 expression in neuronal and non-neuronal cells

Abstract: As the main beta-secretase of the central nervous system, BACE-1 is a key protein in the pathogenesis of Alzheimer's disease. Excessive expression of the protein might cause an overproduction of the neurotoxic beta-amyloid peptide. Therefore, a tight regulation of BACE-1 expression is expected in vivo. In addition to a possible transcriptional control, the BACE-1 transcript leader contains features that might constitute mechanisms of translational regulation of protein expression. Moreover, recent work has rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
89
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(92 citation statements)
references
References 52 publications
2
89
1
Order By: Relevance
“…A previous study (De Pietri Tonelli et al, 2004) has reported the regulation of BACE1 protein expression by upstream ATGs at the translational level and BACE1 translation by the transcript leader in activated astrocytes stimulated with TNF-a or IL-1b. However, our findings of IFN-g-induced BACE1 mRNA and promoter activity indicate that astrocytic BACE1 protein expression is nontranslational effects of IFN-g.…”
Section: Discussionmentioning
confidence: 96%
“…A previous study (De Pietri Tonelli et al, 2004) has reported the regulation of BACE1 protein expression by upstream ATGs at the translational level and BACE1 translation by the transcript leader in activated astrocytes stimulated with TNF-a or IL-1b. However, our findings of IFN-g-induced BACE1 mRNA and promoter activity indicate that astrocytic BACE1 protein expression is nontranslational effects of IFN-g.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, the 5Ј-UTRs of the mRNAs coding for BACE1, APP, and ADAM10 were found to be involved in translational regulation of their downstream gene products (18,71,72). Translational repression of BACE1 is mediated by its long, structured, and upstream ORFs containing 5Ј-UTR (22)(23)(24). Energy deprivation results in phosphorylation of eIF2␣ and consequently in an arrest of global translation; however, BACE1 expression is increased due to reinitiation of translation at the initiation codon of the BACE1 mRNA (25,73).…”
Section: Discussionmentioning
confidence: 99%
“…Translational regulation of specific mRNAs is often achieved by cis-acting elements within UTRs of these mRNAs such as secondary structures, upstream ORFs, internal ribosomal entry sites, and/or trans-acting elements like mRNA binding proteins and microRNAs (19 -21). Interestingly, translation of the ␤-secretase BACE1 is suppressed by its long GC-rich 5Ј-UTR, which contains several upstream ORFs (22)(23)(24). Increased translation of BACE1 was observed in response to energy deprivation, due to increased translation reinitiation at the start codon of the BACE1 message (25), similar to the translation of yeast GCN4 and ATF4 (26,27).…”
mentioning
confidence: 98%
“…There is no evidence to support the idea that the human BACE1 5ЈUTR acts as an IRES element in cap-independent initiation of BACE1 translation (4,36).…”
Section: Discussionmentioning
confidence: 99%
“…1). Recent studies indicate that the upstream AUGs in the 5Ј untranslated region of BACE1 mRNA might have negative effects on BACE1 gene expression at the level of protein translation (4,20,36). However, previous reports re-garding this issue were largely based on experiments using the 5Ј leader sequences of BACE1 mRNA without consideration of its promoter's effect on BACE1 gene expression.…”
mentioning
confidence: 99%